PER CAPITA GROSS REGIONAL DOMESTIC PRODUCT AND NUMBER OF SCHOOL’S PARTICIPATIONT IN - Dwi Setyadhi Mustika, Made (PIRAMIDA; Vol. 5, No.1 Juli 2009, 2012)
This paper discuss about number of school’s participationt (APS), and per capita gross regionaldomestic product (per capita GRDP) in Bali Province, which is analysed using tipologi area. Thedata used are secondary data, consisted of per capita GRDP, number of students from ElementarySchool to Senior High School, and number of population ages 7-19 years, in 9 (nine) regencies/cityin Bali Province. The data obtained from BPS of Bali Province.The result of the research could be elaborated as follows. Badung Regency, Denpasar City, andGianyar Regency are owning per capita GRDP dan number of school’s participant higher than meanof Bali Province. Bangli, Klungkung, Karangasem, dan Buleleng Regency are owning per capitaGRDP dan number of school’s participant lower than mean of Bali Province.
Keywords: per capita GRDP, APS, tipologi area